Mewujudkan Lingkungan Belajar Yang Aman Dari Intoleransi, Kekerasan Seksual Dan Narkoba Di PKBM Mojopahit Kota Mojokerto - M. Bahtiar Ubaidillah; Ragil Ira Mayasari; Irwan Swandana; Titik Khusumawati; Mohamad Johan Efendi; Khasbulloh Huda; Sugeng Eko Yuli Waluyo (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Information about intolerance, sexual violence and drugs is very important material for every good citizen, especially for teenagers. Mojopahit PKBM students are very diverse, but the majority in terms of age, there are still many students who are of productive age (teenagers). In accordance with the Decree of the Minister of Religion of the Republic of Indonesia Number 01 of 2003 concerning Guidelines for Education and Training of Civil Servants in the Environment, the Department of Religion also integrates human rights and gender values ​​in its curriculum. The implementation of this service activity uses discussion/question and answer/introduction and empowerment methods. In order to obtain information and get closer to the service participants, the service team conducted brain storming with the socialization participants. This community service activity targets tutors and residents studying PKBM Mojopahit, Mojokerto City. This service activity was attended by 20 participants from students from package levels A, B and C and several PKBM Mojopahit Tutors from Mojokerto City took part in accompanying the students who attended.